THE MEASUREMENT OF SHARIA GENERAL BANK PRODUCTIVITY IN INDONESIA USING MALMQUIST INDEX - Mutiara Ramadhani Putri; Puji Sucia Sukmaningrum (Universitas Airlangga, 2020)
The development of Islamic bank is increasingly rapid and intense competition is one reason for the importance of assessing the performance of Islamic banks in Indonesia. This research was conducted to measure the level of productivity of Islamic Commercial Banks in Indonesia for the period 2011-2018. Measurement productivity level of Islamic banks can be measured by the Malmquist Productivity Index (MPI). There are 8 Islamic Commercial Banks used as research samples. This study uses an intermediation approach with an output orientation. There are two types of variables used, namely input and output variables. Input variables include: total assets, Third Party Funds, and labor costs. Output variables include: total financing and total investment. The funding of this study is productivity of Islamic Commercial Banks in Indonesia increased during the observation period. The increase was more influenced by the technology change factor (TECHCH) than the efficiency factor (EFFCH). It shows that the increase in productivity of Islamic Commercial Banks is due to the success of Islamic Commercial Banks in managing production using appropriate technology.Keywords: productivity, Islamic commercial bank, Malmquist Productivity Index, Indonesia